FAST-TRACKING DRUG APPROVALS: A SYSTEMATIC REVIEW OF THE US FDA'S EXPEDITED REGULATORY PATHWAYS - NS, PREETHAM; MUNDRA, SARATH; LOPES, NEIL MESSIAH; DUBEY, AKHILESH (International Journal of Applied Pharmaceutics, 2025)
The current review explores the utilization and impact of the United States Food and Drug Administration’s (US-FDA) accelerated drug approval pathways over the past decade (2014–2024). Specifically, it evaluates five key programs: Orphan Drug Designation, Fast Track, Breakthrough Therapy, Priority Review, and Accelerated Approval. The primary aim is to assess how these expedited pathways influence drug development timelines and overall approval success rates. A comprehensive literature search was conducted using databases such as PubMed, Scopus, Web of Science, and Google Scholar. The search yielded 200 articles, of which 110 met the inclusion criteria. From these, 25 key studies were selected for detailed analysis. The findings indicate that Priority Review accounted for the highest number of drug approvals (367 approvals, 55%), followed by Orphan Drug Designation (279 approvals, 42%) and Fast Track (215 approvals, 32%). Breakthrough Therapy and Accelerated Approval contributed to 124 (19%) and 103 (15%) approvals, respectively. These programs have significantly accelerated the availability of essential treatments, particularly in oncology and rare diseases. However, challenges persist. The reliance on surrogate endpoints raises concerns about long-term efficacy, and the need for rigorous post-marketing surveillance remains critical to ensure safety and therapeutic value. In conclusion, the increasing adoption of these accelerated pathways underscores their growing importance in meeting urgent medical needs. While they offer promising benefits in terms of faster access to life-saving therapies, a balanced approach that ensures thorough evaluation and long-term monitoring is essential for sustained public health outcomes.